Analisis Keberlanjutan Wilayah Perbatasan Kalimantan Barat-Malaysia untuk Pengembangan Kawasan Agropolitan (Studi Kasus Kecamatan Dekat Perbatasan Kabupaten Bengkayang) - Thamrin, nFN; Sutjahjo, Surjono H.; Herison, Catur; Sabiham, Supiandi (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2007)
EnglishThe Government of Bengkayang Regency has decided that the border area is one of the agropolitan region development programs. Hence, a study on the sustainability level of border area as the agropolitan region development is required.Â The first objective of this study was to analyze the index and sustainability status of the border area, Bengkayang Regency, based on five sustainable dimensions. The analysis used Multi Dimensional Scaling (MDS) Method, called Rap-BENGKAWAN and the results were stated in the index and sustainability status. The second objective was to analyze the attributes that affect sensitively on index and sustainability status and the effect of error using Laverage and Monte Carlo Analysis. The results of the study revealed that ecological dimension was in the status of less sustainable (40.37%), economical dimension was sufficient sustainable (66.54%), socio-culture dimension was sufficient sustainable (67.06%), dimension of infrastructure and technology was not sustainable (24.49%) and dimension of law and institutional was sufficient sustainable (60,10).Â Out of the 47 attributes analyzed, there were 22 attributes need to be handled immediately as they affect sensitively on the increase of index and sustainability status with a negligible error in the level of 95% confidence limit. IndonesianPemerintah Kabupaten Bengkayang menetapkan wilayah perbatasan sebagai salah satu program pengembangan kawasan agropolitan. Untuk itu, perlu dikaji tingkat keberlanjutan wilayah perbatasan sebagai kawasan pengembangan agropolitan. Penelitian ini bertujuan untuk menganalisis indeks dan status keberlanjutan wilayah perbatasan Kabupaten Bengkayang dari lima dimensi keberlanjutan. Analisis menggunakan metode Multi-Domensional Scaling (MDS) yang disebut Rap-BENGKAWAN dan hasilnya dinyatakan dalam bentuk indeks dan status keberlanjutan. Untuk mengetahui atribut yang sensitif berpengaruh terhadap indeks dan status keberlanjutan dan pengaruh galat, dilakukan analisis Laverage dan Monte Carlo. Hasil analisis menunjukkan bahwa dimensi ekologi berada pada status kurang berkelanjutan (40,37%), dimensi ekonomi cukup berkelanjutan (66,54%), dimensi sosial-budaya cukup berkelanjutan (67,07%), dimensi infrastruktur dan teknologi tidak berkelanjutan (24,49%), dan dimensi hukum dan kelembagaan cukup berkelanjutan (60,10%). Dari 47 atribut yang dianalisis, 22 atribut yang perlu segera ditangani karena sensitif berpengaruh terhadap peningkatan indeks dan status keberlanjutan dengan tingkat galat (error) yang sangat kecil pada taraf kepercayaan 95%.